Placenta accreta spectrum: ultrasound diagnosis and clinical correlation - Mariana Tsankova; Mila Kirkova; Nikolay Geshev (Biotechnology & Biotechnological Equipment)
The abnormal invasive placenta is a unique pathological condition, and it occurs only in humans. The definitions, classifications, and ultrasound markers for pathological placental attachment are being developed to unify and standardize. Placenta accreta spectrum (PAS) is a clinical situation rather than an isolated condition in which the placenta does not separate spontaneously from the uterine wall after the delivery of the fetus, and all added forceful methods for its separation lead to massive life-threatening hemorrhage. Morbidity and mortality in such situations are increasing; therefore, the involvement of a multidisciplinary team is important. The main risk factors are previous caesarean section and placenta previa. The PAS rate increases in proportion to the increase in the frequency of Sectio Caesarea (SC). The final diagnosis is made by ultrasound Grayscale color Doppler and 3D in the third trimester after 28–30 weeks of gestation. The most common and correct treatment is peripartum hysterectomy. This mini-review provides an overview of PAC, interpreted as a life-threatening disorder (the new terminology for placenta accreta). We present ultrasound findings collected over an 11-year prospective period of examination of over 58 cases of placenta accreta, of which 53 ended with peripartal hysterectomy and 5 partial accreta, which ended with preservation of the uterus, histologically approved. The markers of PAS are presented based on the criteria of FIGO and ACOG in correlation with intraoperative findings and pathohistological examination.